Nepalesiske bloktryk - Jacobsen, Werner (Kuml, 1959)
Nepalese Woodcuts. Where Nepal is here named it is not to be understood as the land of Nepal as it now appears on the map, but rather the very fertile valley, the largest in the Himalaya, in which lies the capital of the country, Kathmandu. Not only was in earlier days the term Nepal synonymous with the Kathmandu valley, but even to this day the Kathmandu valley, with its urban civilisation, is referred to as Nepal by the surrounding mountain peoples. It should be said at once that the woodcuts are by no means a valid example of the excellence of Nepalese craftsmanship. They represent rather its lowest level, and the reason for their treatment here is first and foremost that they are faced with an imminent defeat and complete disappearance in the struggle with modern printing machines. And secondly that they present a living picture of the religious life which is unfolded among the ordinary people of the Kathmandu valley. With but few exceptions the woodcuts are associated with religious festivals and ceremonies, and a description of some of the most important of these will therefore now be given. The Buddhist scripture "Kriya Samuchchaya" records the saying of the Buddha, "Worship the Nagas, and also Varuna, on the fifth day in the lighter half of Srawan. This counteracts all devilry occasioned by snakes and promotes a plentiful rainfall!" The written authority of the Hindus is the "Garuda Tantra", in which Vishnu commands, "Paste with cow manure pictures of the Nagas over the entrance to the house and over the other doors of the house on the fifth day of the lighter half in the month of Srawan, and worship the snakes in accordance with the ritual prescribed.'' In agreement with these commands this "day of the snakes" is observed by Hindus and Buddhists alike, and coloured woodcuts, large and small, representing the Nagas, the snakes, are pasted up over the house entrance and the other doors. This type of block printing is here represented by Fig. 1, an original woodcut showing Kanya Nagini, the snake virgin, a particularly popular subject within this group of woodcuts. The popularity of this figure is undoubtedly due to the fact that she is the counterpart, in the world of the snakes, to Kanya Kumari in the world of men. And Kanya Kumari is particularly widely worshipped in Nepal. She is the divine virgin, an aspect of Parvati, and in Nepal is represented by several living personifications, of whom the deadly serious little Kumari who resides in her own palacetemple opposite the old royal palace in the centre of Kathmandu is regarded as the most distinguished. After a somewhat brutal process of selection each new Kumari is installed, normally at an age of 5-6, and retains her divine position until the commencement of puberty, when a new Kumari is selected. The Sanskrit text on the woodcut, Fig. 1, is a somewhat abbreviated form of a standard text which normally, either in full or abridged, occurs on the Naga prints. After a prefacing invocation of Ganesha, the elephant god, which normally introduces religions texts, the inscription reads in its complete form: "The saints Agastya, Pulastya, Vaisampayam, Sumanta and Jaimini are the five protectors of the thunderbolt. There are eight Nagas, whose names are Ananta, Vasuki, Padma, Mahapadma, Tahshaka, Kulika, Karkotaka and Sankha." According to the "Vishnu Purana", Kadru, one of Kasyapa's thirteen wives and a granddaughter of Brahma, was the mother of a thousand multi-headed snakes, who were organised under twelve chieftains. Other texts, like ours, name eight important Nagas. The companies of the snakes inhabit the underworld, the seas and the lakes, together with scorpions, centipedes and other crawling things. Hindu mythology is full of legends of the power and cunning of the Nagas, whom it is best to keep on good terms with, and for the dwellers in the Kathmandu valley the myths have a particularly awesome immediacy. For in the local "Swayambhu Purana" it is told that the lake, which in former days filled the valley, was the home of Karkotaka Naga and many other snakes. The Nepalese therefore live in constant awareness of having driven these dangerous creatures from a well-loved dwelling place, and it is consequently necessary for them to make special efforts to reestablish good relations. As is natural where a numerous population lives within a very limited agricultural area, the food situation within the valley is the problem which overshadows all else. As the text quoted above from the "Kriya Samuchchaya" suggests, the Nagas, if not placated, are likely to attack at the weakest point, to cut off the lifegiving rainfall. And against this background it is hardly surprising that in the light half of the month of Srawan there is a great demand for the woodcuts representing the various Nagas, and that on the fifth day, as the old scriptures prescribe, they are pasted up with care over every door. In this nationwide exhibition of snake portraits the popular hero-god Krishna is often to be seen. As so often when human freedom is in danger, he comes to the rescue. With his flute he charms the eight deadly snake-kings who, united in a rigid geometrical pattern, cancel out each other's powers and become thereby powerless to harm mankind. This scene is here represented in the beautiful woodcut reproduced as Fig. 2. Throughout the year the gate to the Nepalese heaven, Yama Dwar, remains closed, and it may be believed that among the gradually increasing number of the dead who wait outside that one day in the year when the door stands a little ajar is looked forward to with eager anticipation. That day falls on the first day of the dark half of the month of Srawan (in 1958 the 30th August). Unfortunately for the dead, the door does not open enough for them to pass through, and experience shows that only the cow it able to push back the heavy door with its horns. It is to help here that the ceremony of Gaii Jatra (Sa-Paru in Newari) is observed on this day. Every family in which a death has taken place during the past year sends a cow, or one of the family decked out as a cow, to help the dead into heaven. For the masquerade in Kathmandu a headdress is used consisting of a flat woven basket bearing on the front a coloured woodcut of a cow's head (Fig. 3) and on the back a woodcut of Ganesha (Fig. 4). On either side of the headdress there is a thin wooden or bamboo upright bearing coloured paper flags and fan-like decorations, while on the basket is attached a group of three miniature cow's horns of woven straw. The disguised person draws behind him a long cloth train, on which gifts to the dead in the form of fruit and cakes are placed. In Kathmandu Gaii Jatra is held as a private family festival, and separate processions of men dressed as cows, or in the case of the richer families actual cows, wend through the streets accompanied by flute and drum. In Lalitpur (Patan), on the other band, all participants unite in one large procession and set off to the assistance of the dead accompanied by many orchestras; and here the "cows" pull in their train pots and pans and other household goods. Of all the many motives treated in the Nepalese woodcuts the cow's head for the Gaii Jatra ceremony is of the highest decorative effect (Fig. 3). The block is cut with clear powerful lines, and the colouring is carried out with a sure feeling for dramatic combination. That we find the elephant god, Ganesha, (Fig. 4) taking part in this ceremony should not surprise us, for the son of Siva and Parvati is ubiquitous in Nepal. No festival is held, no ceremony celebrated without his participation. And nowhere can his assistance be more desirable than when it is a question of helping a clear, but not necessarily deserving, departed in through the heavenly portals. For Ganesha, the god of wisdom, is also the overcomer of obstacles. It is said, and not entirely without reason, that in Nepal every day of the year has its own festival or ceremony. But surely no event is anticipated with more unmixed pleasure than the yearly ceremony in honour of the goddess of wealth, Lakhsmi. For Lakhsmi Puja is a true festival, free of the nagging apprehension of the Naga Panchami, the melancholy recollections associated with the Gaii Jatra, or the macabre and expensive aspects of the festivals demanding blood sacrifices. The morning is sacred to the cow, which receives offerings and is adorned with flowers. Thereafter all windows and doors in the newly cleaned house are decorated, incense is burnt, and at nightfall innumerable lamps are lit inside and out. Surrounded by the entire family in its finest clothes, the head of the family carries out the various rituals of offering to Lakhsmi. Coloured woodcuts of the goddess of wealth (Fig. 5) are pasted on the cashbox, and before her picture are placed offerings of money, fruit and sweets. Included among these are various amusing figures of sugar, bright red or green, which the Nepalese children, with their usual practical good sense, interpret as special gifts to themselves from the goddess. And in the days following the Lakhsmi Paja every child in the valley goes around with violently coloured tongue and lips, and with a somewhat uncertain feeling in its stomach. On the floor in front of the picture of the goddess a Mandala is formed, a circular place of offering divided into sections containing five different sorts of corn, five colours, the eight holy symbols and vases of water. Sometimes a coloured woodcut (Fig. 6) is substituted for this, showing Lakhsmi sitting in the centre of a Mandala, surrounded by persons bringing offerings. This is what - depending on temperament or ones personal interest in the matter - is called "symbolical substitution" or "trying to cheat the gods". However it be judged it is a procedure common enough all the way from gray antiquity up to our own day, and is after all no less understandable than the view that paper money is worth more than the paper on which it is printed. The woodcut of Lakhsmi (Fig. 5) illustrates the elements of which modem Nepalese art is composed. The sari in which the goddess is clothed is lndian, China is represented by the little man with Chinese beard and mandarin cloak, while the lions' heads and ornamentation of the throne and the stucco pillars in the background reflect the triumphal progress, regrettable but enthusiastically welcomed, of the European Victorian style through the ancient culture lands of the East. The purely Nepalese element, somewhat unpretentious in this case, is represented by the two gnome-like dwarfs, who are called Kyats and belong to the numerous and variagated families of dwarfs, trolls and ghosts who inhabit the valley. In their white form they are friendly disposed and help Lakhsmi to carry the heavy moneybags. But in their black shape they are full of supernatural powers which they use with zeal for the ruin of mankind. We have now to a great degree described the woodcuts which are still in use. A large number of old blocks are, however, preserved which are no longer used for printing, but whose motifs can be ascribed to definite festivals and ceremonies, although it is no longer possible to trace their original function in these ceremonies. The cut of an old block from Bhaktapur, reproduced as Fig. 7, shows the goddess Durga struggling with the buffalo-demon Mahishasura, and it can hardly be doubted that this woodcut was originally used in connection with the bloody ceremony of Maha Navami, which falls on the ninth day of the light half of the month of Aswin (in 1958 the 21st October). The Newars call this festival Syako Tyako, which means "Kill as many as you can", an invitation which few ignore. The festival celebrates the victory of Durga over Mahishasura, and before the numerous statues in the valley of this bloodthirsty lady are sacrificed innumerable victims, preferably buffaloes, as they are regarded as symbols of Mahishasura. Fig. 8 reproduces a cut from another old block, probably from Kathmandu. We recognise here the central scene as the Kija Puja, the brother-worship ceremony which is held each year on the 27th day of Kartic (in 1958 the 12th November). The seated brother accepts offerings of food and drink from the sister standing before him. The origin and significance of this ceremony is obscure, but it would seem to be a parallel to the many ceremonies which serve to confirm the connection between the individual and the caste. In a similar way other ceremonies serve to emphasize other connections and relationships of the individual, in this case the bond between brother and sister. The feeling of belonging to a group, represented by the family and the caste, is a strong and ubiquitous motif in the life of the valley, clearly symbolized in the caste ceremony, where a long cotton thread is passed through the hands of all the participants, until the ends of the thread meet again. The two figures flanking the central scene of the woodcut can be identified as the Yama Dutas, the emissaries of Yama, the god of death. With weapon in the right hand and rope in the left they bind the victim and bring him to judgment before the god, but here they stand waiting, powerless to disturb the ceremony. This may give us some idea of the original thought behind the symbolism: unity is strength, but he who stands alone is an easy prey for the greedy messengers of Yama. This interpretation rests on a somewhat uncertain basis, but is supported by the fact that individuals were chosen as human sacrifices who, voluntarily or involuntarily, were separated from their families or relationship groups, vagabonds and prisoners of war. It now remains to deal briefly with the actual woodcuts and their producers. The blocks are cut by specialists of the Urär caste, and the material is, with only one known exception, wood. There would appear at times to have been a shortage of suitable wood of sufficiently large size, for some of the larger blocks can be seen to have been put together from two or more pieces, but this may also be the result of economy on the part of the block cutter. The construction shows that the explanation for this practice cannot have been a desire to prevent the block from warping, and in any case warping presents no problem, as the method of printing does not require that the printing surface be exactly plane. The importance of clay in the life of the valley is enormous, and it is used, not merely as a basis for agriculture, but for a variety of purposes extending from building material to shampoo for the women's hair. It can therefore occasion no surprise that the exception mentioned above is a printing block of sun-dried clay (Fig. 9). The size of the block is 15.5 X 18.5 X 3 cms., its motif the goddess Lakhsmi. It is a unique specimen, and it cannot be determined whether it is the result of an isolated experiment or whether it represents a period when clay was used generally as a material for blocks. From the wood carver the printing block goes to the artist, who belongs to the Pung caste. To preserve its strength and durability it is given a bath in oil (of mustard seed) before printing commences. The printing ink is made from a mixture of lamp-soot, gummi arabicum (saresh in Nepali and Newari) and water, the correct consistency being obtained by a slight warming. The block is placed on the floor with the printing surface uppermost, and the ink brushed on. The paper is then laid over the block and smoothed over with the hand. The paints for colouring the print are prepared in the same way as the printing ink but are of a more fluid consistency to allow of application with a brush. The pigments now used are all imported chemical colours, but originally natural vegetable and mineral pigments were employed. Colour application is carried out on the "assembly-line" principle, one colour at a time, and here the artist is often assisted by the children of the family. Some time in advance of each festival or ceremony for which the woodcuts are used the artists begin to manufacture an appropriately large edition, never larger than they estimate can be sold in the course of the coming festival, for from then until the following year's festival there will be no possibility of further sale. The day before the festival members of the artist's family station themselves on the street surrounded by bundles of the print. Each type of woodcut is normally offered for sale in a number of variations, for even the Nepalese block printer has learnt by experience that to succeed in a competitive society they must have something for every taste, and not least for every purse. The size of the woodcuts varies, as would be expected, according to their use. The largest prints are the Naga pictures, which are to be pasted on the house facades during the Naga Panchami. They measure up to 55 X 45 cms. Next in order of size come the cows heads for the Gaii Jatra ceremony in Bhaktapur, which reach a size of 46 X 30 cms., while the more modest cows in Kathmandu and Lalitpur must be content with heads of about 28 X 23 cms. As there is unfortunately a natural limit to the size required for the cashbox of the average family, and as the Lakhsmi prints are designed to be pasted upon these, the prints for this ceremony do not occur in large format. The largest are 21 X 17 cms., but they are found in all sizes down to 4 X 5 cms., which reflects the uneven distribution of this world's goods. We have several times referred to the block printer as an "artist". This must not be understood as an attempt to raise his products to a higher plane. The explanation is that block printing is only a branch of his work. His profession is that of artist, Chitra Kar. He it is who decorates the masks of the devil dansers, the gigantic umbrellas of the processions, the round sides of the marriage jars, and many other objects of ceremonial use. His future is uncertain, for also in Nepal will mechanical methods take the place of the ancient craftmanship. The time is not far distant when the block printer himself will only have need for the very smallest of the pictures of Lakhsmi to paste upon his shrunken cashbox, and even that will probably have been produced upon a rotation press. Werner Jacobsen